A modified method to reduce variable outcomes in a rat model of four-vessel arterial occlusion. (1st December 2016) - Lu, Dan; Wu, Yingxi; Qu, Yan; Shi, Fei; Hu, Jun; Gao, Bo; Wang, Bao; Gao, Guodong; He, Shiming; Zhao, Tianzhi
Abstract : Objectives: Rat models of global cerebral ischemia (GCI) are essential to study potential treatment strategies against stroke in humans. However, nonvisual electrocoagulation of vertebral arteries often leads to incomplete occlusion that may prevent the creation of a successful model. Methods: Therefore, we used a modified method in which the vertebral arteries were safely visualized and electrocauterized between the first and second transverse processes through a dorsal incision. Twenty-four hours later, GCI was induced by transient bilateral common carotid arterial occlusion using microvascular clips. The clips were removed after 10, 20, or 30 min of four-vessel occlusion. Results: Digital subtraction angiography demonstrated complete occlusion of the rat vertebral arteries. In the 20-min GCI group, the rats were monitored for 1, 3, 5, or 7 days followed by histological analysis. The results showed that neuronal death in the CA1 subregion occurred almost linearly between 1 and 3 days of recovery. Tape removal test was used for up to 7 days after 20 min of GCI or sham operation. The latency time was found to be significantly increased 1 to 7 days after GCI compared with sham. Conclusions: In conclusion, this modified model provides a reliable tool for ischemic stroke research.